Teff Value Chain in Ethiopia: Producer/Household Survey - International Food Policy Research Institute; Ethiopian Development Research Institute (International Food Policy Research Institute, 2020)
The producer/household survey was conducted to study teff value chains in order to make recommendations to policymakers on how to improve the value chain for farmers, wholesalers, retailers, and consumers in Ethiopia. The data collected in this survey helps to understand how the teff value chains are transforming in terms of quality and demand of teff, adoption of modern inputs in teff farming, farmers' access to inputs and services, their income and wealth among many other things.